PERBANDINGAN KARAKTERISTIK MARSHALL CAMPURAN BETON ASPAL AC-WC FILLER SEMEN PASCA PERENDAMAN DI AIR SUNGAI DAN DI AIR LAUT - Sulfiati; Hasanuddin; Andira, Ayu (Fakultas Teknik Universitas Muhammadiyah Palu, 2024)
Water/puddle is one of the causes of damage or reduces durability for road construction with asphalt pavement. Several roads in Indonesia which are close to the coast experience problems with sea water inundation which is mostly caused by extreme weather, resulting in tidal flooding or what is known as tidal water. The purpose of this study was to compare the changes in Marshall characteristics of asphalt concrete mixture AC-WC filler cement due to post-immersion in river water and in sea water with different variations of soaking time. The characteristics measured using the marshall tool are stability, flow (melting) and Marshall Quetiont (MQ). This study uses experimental methods in the laboratory. Immersion of test object samples (brickets) in river water and in sea water with variations in immersion time of 0.5 hours, 24 hours, 48 hours, 96 hours and 168 hours. To determine the ratio of changes in strength and durability of asphalt concrete mixture Ac-Wc. The results indicate that post-immersion in sea water for a long time has a greater effect as a destroyer of asphalt layers than river water. For post-immersion in river water, stability values were obtained from 0.5 hours to 168 hours, flow values from 0.5 hours to 96 hours and MQ from 0.5 to 96 hours. While the results after immersion in sea water obtained stability values from 0.5 hours to 168 hours, flow values from 0.5 hours to 96 hours and MQ from 0.5 to 48 hours. Of the two types of immersion, the longer the asphalt concrete mixture is immersed in river water or in sea water, both of them can reduce the strength and durability of the mixture. Because seawater contains a lot of NaCl which is an aggressive ion and affects the loss of the bond between aggregate and asphalt.